2022
DOI: 10.3390/cells11192988
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment of Retinoic Acid Plus Focal Adhesion Kinase Inhibitor Prevents Tumor Growth and Breast Cancer Cell Metastasis

Abstract: All-trans retinoic acid (RA), the primary metabolite of vitamin A, controls the development and homeostasis of organisms and tissues. RA and its natural and synthetic derivatives, both known as retinoids, are promising agents in treating and chemopreventing different neoplasias, including breast cancer (BC). Focal adhesion kinase (FAK) is a crucial regulator of cell migration, and its overexpression is associated with tumor metastatic behavior. Thus, pharmaceutical FAK inhibitors (FAKi) have been developed to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 81 publications
1
3
0
Order By: Relevance
“…We found that Lp, T-DM1, and combined treatments induce nuclear FAK translocation in BT-474 and SKBR3 cells. FAK redistribution from the cytoplasm to the nucleus in response to stress agents has been previously reported by our group and others [36,39,67,68]. In addition, anti-HER2 treatments increased perinuclear cortactin, most highly in combined therapies.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…We found that Lp, T-DM1, and combined treatments induce nuclear FAK translocation in BT-474 and SKBR3 cells. FAK redistribution from the cytoplasm to the nucleus in response to stress agents has been previously reported by our group and others [36,39,67,68]. In addition, anti-HER2 treatments increased perinuclear cortactin, most highly in combined therapies.…”
Section: Discussionsupporting
confidence: 76%
“…Absorbance at 570 nm was measured using a microplate reader (MULTISKAN EX; Thermo Scientific). Cell viability was calculated as a percentage of viability in treated cells compared to untreated cells, as described by Castro-Guijarro et al (2022) [36].…”
Section: Cell Viabilitymentioning
confidence: 99%
See 2 more Smart Citations